PO 18146 - The efficacy of a diabetic educational program and predictors of compliance of patients with non-insulin dependent diabetes mellitus (type 2) - Cristina Stéfani, Kelly; Barbachan Rodrigues, Aldo; Quadros Borges, Vinicius; Ferraz Ferreira, Gabriel; de Matos Moraes, Leonardo Vinícius (Scientific Journal of the Foot & Ankle, 2019)
Introduction: Diabetes mellitus (DM) has become a global public health problem. The concept of detection and management of diabetes mellitus in primary care centers is widely practiced in Brazil by the general practitioner. The aim of this study was to evaluate the efficacy of our educational program for diabetics for patients with diabetes mellitus and to determine the predictors of compliance. Methods: A cross-sectional prospective study was performed in a quaternary hospital where patients with diabetes were referred to the outpatient clinic of the diabetic foot group so that they were part of a multidisciplinary group (medical orthopedists specialists in foot and ankle, medical endocrinologists, physiotherapist and nurse) with a specific protocol for guidelines for foot care. Specialist orthopedic doctors of the foot and ankle completed the protocol and performed the specific physical examination. Results: Of the 578 diabetic patients, the mean age was 67 years, 69% were female, 53% used insulin to control the disease and the disease duration was 14 years. Obesity was diagnosed by calculation of the body mass index (BMI), and 85% patients were overweight. Evaluation of protective sensibility showed that 68% were significantly decreased, with sensation from the 4.0 g monofilament. One hundred and twenty seven patients required surgery resulting from clinical complications of the disease: 64 ulcers (Wagner classification 57% ulcers had a degree 1 Wagner classification, 63% affected forefoots), 54 Charcot arthropathies (52% Eichenholz in phase 3, 61% located in the mid-foot), and 9 cases of osteomyelitis. Fifty-three patients had one or more prior amputations at the time of their first appointment, mostly of the toes (66%). Conclusion: The costs related to the disease increased greatly with the appearance of complications, especially if there was a need for hospitalization and surgical treatment. The prevention of injuries with adequate glycemic control and the provision of protective shoes is essential.